Diseño de libros electrónicos para la enseñanza a distancia a estudiantes con diferentes capacidades matemáticas - Gutiérrez, Ángel (2021)
Distance learning is gaining importance because of the restrictions on face-to-face teaching due to the covid-19 pandemic. But it is necessary to propose a form of distance teaching different from the traditional one, which is flexible and integrated with face-to-face teaching. Interactive e-books are an interesting tool for primary and secondary school teachers to organize their teaching by combining the presence of children in the classroom and study at home. In this lecture I present an example of this form of distance learning, using an interactive e-book designed for use by students in or out of the classroom. The book presents the symmetries of the plane using the guided discovery methodology and organized according to Van Hiele's levels. In addition, the book offers several itineraries through its activities, suitable for students with difficulties, medium and high mathematical ability.